Design of Kocerin (Smart box interactive) Media basic character building on fraction material in the islamic yunior high school - achmad buchori buchori (Jurnal Informatika Upgris, 2016)
abstractChildhood is the Future of the nation should nourished the soul and soul to a review of Children Become Smart, Skilled And Good character. Early child Age Class 7 MTs should be developed gross motor and fine motor skills through play activities. One of Duties and Obligations For the teacher is Constantly working to improve the quality of education by having innovation-innovation learning The prayer only is with using Media Learning to appeal for Students, praying only Media is kocerin (smart box Interactive) That can be motivating students to review more Understanding A problem Shape Game The proposed hearts and can be cause of imagination and creative thinking stimulus prepare Son.This research is R & D to develop a media review Kocerin For Students MTs / SMP. Research shows that the product has been validated by 2 kocerin orangutan expert validator material and Learning Media with score  averaged 93.5 and 95.5 means that products used kocerin feasible to review Learning Process in MTs, has applied MTsN 2 Semarang, response then children Very Enthusiastic WITH percentage More Than 90% children Enthusiastic follow with learning Media with smart box interactive in MTsN 2 Semarang.Keywords: Kotak cerdas interaktif, Fractions, MTs